Assessment of rhizospheric culturable bacteria of Phragmites australis and Juncus effusus from polluted sites. (8th June 2015) - Pereira, Sofia I.A.; Pires, Carlos; Henriques, Isabel; Correia, António; Magan, Naresh; Castro, Paula M.L.
<x xml:space="preserve">Abstract</x> This study aimed at the isolation and characterization of metal(loid)‐tolerant bacteria from the rhizosphere of Phragmites australis and Juncus effusus plants growing in two long‐term contaminated sites in Northern Portugal. Site 1 had higher contamination than Site 3. Bacteria were isolated using metal(loid)‐supplemented (Cd, Zn, and As) media. Isolates were grouped by random amplified polymorphic DNA and identified by 16S rRNA gene sequencing. Strains were also examined for their metal(loid) tolerance. The counts of metal(loid)‐tolerant bacteria were higher in Site 1 and ranged between log 7.17 CFU g−1 soil in As‐containing medium and log 7.57 CFU g−1 soil in Zn‐containing medium, while counts at Site 3 varied between log 5.33 CFU g−1 soil in Cd‐containing medium and log 6.97 CFU g−1 soil in As‐containing medium. The composition of bacterial populations varied between locations. In Site 1, the classes Actinobacteria (36%) and Bacilli (24%) were well represented, while in Site 3 strains were mainly affiliated to classes Actinobacteria (35%), γ‐Proteobacteria (35%), and β‐Proteobacteria (12%). The order of metal(loid) toxicity for the isolated strains was Cd > As > Zn. Overall, 10 strains grew at 500 mg Cd L−1, 1000 mg Zn L−1, and 500 mg As L−1, being considered the most metal(loid)‐tolerant bacteria. These strains belonged to genera Cupriavidus, Burkholderia, Novosphingobium, Sphingobacterium, Castellaniella, Mesorhizobium, Chryseobacterium, and Rhodococcus and were mainly retrieved from Site 1. The multiple metal(loid)‐tolerant strains isolated in this study have potential to be used in bioremediation/phytoremediation.